Prisoners of War, Prisoners of Peace. - Moore, Bob (Berg Publishers, 2005)
Millions of servicemen of the belligerent powers were taken prisoner during World War II. Until recently, the popular image of these men has been framed by tales of heroic escape or immense suffering at the hands of malevolent captors. For the vast majority, however, the reality was very different.